Efficacy of small-diameter core decompression with platelet-rich plasma in early osteonecrosis of the femoral head: a retrospective study - Haiwei Tang; Yahao Lai; Enze Zhao; Kai Zhou; Gang Chen; Zongke Zhou (BMC Musculoskeletal Disorders)
Abstract Background Osteonecrosis of the femoral head (ONFH) is a challenging condition, primarily affecting young and middle-aged individuals, which results in hip dysfunction and, ultimately, femoral head collapse. However, the comparative effectiveness of joint-preserving procedures, particularly in the early stages of ONFH (ARCO stage I or II), remains inconclusive. This study aims to evaluate the efficacy of a novel technique called small-diameter core decompression (CD) combined with platelet-rich plasma (PRP), for the treatment of early-stage ONFH. Methods Clinical data of 40 patients (51 hips) with pre-collapse stage ONFH were retrospectively analyzed. Nineteen patients (23 hips) underwent small-diameter CD + PRP (group A) and 21 patients (28 hips) received conventional CD (group B) and follow-up was conducted every 3 months. Hip radiographs (X-rays and MRI) were evaluated using various ONFH staging systems (Preserved Angles, ARCO, JIC, and CHFJ stages). X-rays were performed at each follow-up to assess femoral head collapse and the rate of total hip arthroplasty (THA). Additionally, the Visual Analogue Scale (VAS), Harris Hip Score (HHS), Charnley score, SF-36, Athens Insomnia Scale (AIS), and State-Trait Anxiety Inventory (STAI) were used to evaluate hip pain, function, quality of life, and psychological status. These assessments were conducted both preoperatively and at each follow-up visit. Results The mean follow-up duration in Group A was 11.57 months, with a femoral head survivorship of 82.61%. One hip underwent THA 14 months after the novel procedure. In Group B, with an average follow-up period of 11.32 months, femoral head survivorship was 60.71% (p = 0.111), and 2 hips required THA (p = 0.999). At the final follow-up, the VAS, stiffness, HHS and Charnley scores of Group A showed significant improvements compared to those in Group B. Quality of life, anxiety and insomnia were also significantly improved in the Group A compared to Group B. Conclusion The application of PRP following CD results in significant pain relief, improved short-term functional outcomes, and enhanced quality of life compared to CD alone. However, whether it hinders disease progression in early ONFH and reduces the conversion rate to THA and femoral head collapse remains uncertain. Further research with larger sample sizes and extended follow-up is needed to validate these preliminary findings.